Curse-Practices in the Late-Antique Roman Levant and North Africa - Gordon, R. L. (Religion in the Roman empire, 2021)
This is the second issue of Religion in the Roman Empire devoted to the practice of depositing written curses at charged or subjectively significant locations. Here we present revised versions of seven of the fifteen papers delivered at the second Curses in Context conference, organised by Christopher A. Faraone and Sofía Torallas Tovar at the Paris Centre of the University of Chicago, 17-18 September 2018, with the sponsorship of the university's Neubauer Collegium. Two further papers that were not given at that conference have been added, while the tenth, by Roger Tomlin, is frankly an outlier, since it was intended for the previous issue but for technical reasons could not be included in it.